THE EFFECT OF GOOD CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE IN THE LQ45 INDEX LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2017-2021 PERIOD - Rizka Ariyanti; M Iqbal Notoatmojo; Eriza Safitri (Dinamika Akuntansi Keuangan dan Perbankan, 2022)
This study aims to determine how the influence of Good Corporate Governance with indicators of institutional ownership, independent commissioners, and audit committees on the financial performance of LQ45 companies for the 2017-2021 period. The method used in this study is a descriptive method with a quantitative approach. Sources of data used in this study are secondary data sources. Statistical analysis used in this study is multiple linear regression analysis. Based on the results of the analysis, it can be seen that institutional ownership has a significant positive effect on financial performance (ROA), while the independent board of commissioners and audit committees have a significant negative effect on financial performance (ROA). Companies must balance share ownership between management and institutions so that there is no majority or minority party, all are responsible for making policies so that both can increase the value of the company.